Možnosti uporabe robotike v rehabilitaciji zgornjega uda pri osebah z okvaro hrbtenjače - Kidrič, Urška (Rehabilitacija (Ljubljana), 2022)
In the rehabilitation of people with spinal cord injuries in the cervical region, robotics is used as a supplement to classical, established neurophysiotherapeutic and occupational-therapy procedures. Potential benefits include increased repetitions and assistance in motor performance. With providing support and proper upper limb movement pattern, the robots can help weakened muscles, impaired proprioception and performance. However, the level of evidence is low due to the small number of studies as well as the lack of randomised controlled trials. It will be necessary to plan randomised controlled trials, which will determine the effectiveness of the use of robotics in the rehabilitation of the upper limb in spinal cord injuries.
Keywords: poškodba hrbtenjače; rehabilitacija; rehabilitation; Robotics; robotika; Spinal Cord; spinal cord injury; upper limb; zgornji ud